RULE OF LAW, TRUST, AND COMPETITION: WILL SPED-PRO BECOME A GAME-CHANGER FOR THE PROTECTION OF EU FUNDAMENTAL VALUES? - Grabowska-Moroz, Barbara (Pravni zapisi, 2022)
The CJEU’s jurisprudence based on the LM case has been criticized on the grounds that it is very difficult, if not impossible, to prove threats to due process in an individual case. The central question posed is the permissibility of limiting the principle of mutual trust between Member States because of a potential breach of fundamental rights in one of them. In the recent Sped-Pro case, the General Court decided to apply the above question to a new field of EU Law – competition law – without changing much of the essence of the question. In trying to protect mutual trust between Member States, the General Court has not created effective tools to protect the rule of law in the Member States. This also puts the principle of mutual trust at risk.
Keywords: rule of law; competition law; Court of Justice of the European Union; European Union; mutual trust